Knowledge Regarding Basic Life Support (BLS) among Health Care Workers in Dhamar, Yemen: A Cross-Sectional Study - Salah , Mohammed Kassim; Mokdad , Abdul Salam Mohamed Al; Aljarmouzi, Hussain Mohammed; Al-Ashmali , Omar Yahya; Al-Zaazaai, Ali Ahmed (Recent Updates in Disease and Health Research Vol. 7, 2024)
Objectives: Appropriate BLS is crucial for outcomes of sudden cardiac arrest and traumatic cases. The simple skills a trained BLS provider should have can reduce the high mortality rate associated with cardiac arrest in patients with cardiovascular disease. Aim: This study aimed at evaluating the knowledge of BLS among health care workers working in various departments of health care in the Dhamar governorate, Yemen. Subjects and Methods: The study of knowledge of BLS was performed in Dhamar governorate with a total of 149 graduated health care professionals, including graduated doctors and nurses. The study was performed during the period from May 2019 to Nov 2019. Data were collected through a questionnaire, which is according to the current American Heart Association (AHA)/European Resuscitation Council (ERC) guidelines of 2015. This self-explanatory questionnaire of 24 questions was designed to assess and compare the knowledge of BLS by the participants and consisted of two main domains: demography (composed of 4 questions) and knowledge of BLS (composed of 20 questions). Comparisons of the characteristics of demographic domains- gender, qualification, and previous training in BLS - in terms of the mean score of knowledge were considered and statistically tested by independent- samples t-tests post-Leven's tests. Results: Of the 149 respondents, 97 (65%) had a BLS knowledge score of at least 50% mark, corresponding to adequate knowledge about BLS, and 52 (35%) had a BLS knowledge score of less than 50% mark, corresponding to inadequate knowledge about BLS. The total mean score of BLS knowledge was 53.12 in the setting of a range of 0 - 100 with a standard deviation of 15.58. Statistically, the mean score among males and female participants was found to be non- significantly different, as was the mean score among participants who had ever had previous training in BLS and those who had never had any previous training in BLS. In the present study, medical participants had significantly high knowledge of BLS in comparison with nurses. On the other hand, the mean score in participants who belong to the medicine field was significantly slightly higher than that in participants who belong to the nursing field. Conclusion: Among healthcare professionals, planned BLS training were not very common. Furthermore, there was no correlation found between these courses and sufficient BLS knowledge. Thus, it is advised that health professionals undergo regular reassessments during their careers and that a top-notch, stringent BLS accreditation program be added to the undergraduate curriculum. We also recommend the conduction of studies entailing a comparision of doctors and nurses in terms of knowledge of BLS and the effectiveness of structured teaching programs/video-assisted teaching programs on the knowledge and skills of medical professionals.